Pelaksanaan Gema Haji dalam Menanamkan Karakter Dimensi Profil Lulusan pada Murid Kelas IV di SD Negeri 1 Kembang Sari - Nopsya Aluramadhan Kusuma; M. Deni Siregar; Fadhilah Ningrum Haryanto; Muh. Sofyan Hariri (Mataram University, 2026)
Character development through religious habituation activities is one of the efforts implemented by schools to support the strengthening of the Graduate Profile Dimensions among students. One form of such habituation is the Gema Hajj program, or the massive movement of congregational dhuha prayer and Qur’an recitation, which is conducted regularly at school. However, studies regarding its implementation and the forms of character development based on the Graduate Profile Dimensions remain limited. This study aims to examine the implementation process of the Gema Hajj program and the forms of character development based on the Graduate Profile Dimensions among fourth-grade students at SD Negeri 1 Kembang Sari. This research employed a descriptive qualitative approach that emphasizes the interpretation of phenomena in a natural and holistic manner. Data were collected through observation, interviews, and documentation involving an Islamic Religious Education teacher, a fourth-grade homeroom teacher, and fourth-grade students selected through purposive sampling. Data analysis was conducted using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings show that the Gema Hajj program is implemented daily in the school prayer room, consisting of congregational dhuha prayer, dhikr, collective supplication, and the reading and memorization of selected short chapters of the Qur’an, while on fridays additional activities include the recitation of Surah Yasin, religious lectures, and short speeches. Character development based on the Graduate Profile Dimensions was analyzed through students’ behaviors during the implementation of the program. The results indicate that the dimensions of faith and piety toward God Almighty, independence, communication, and health were evident, whereas citizenship, critical reasoning, and collaboration were less evident, and creativity was not observed. These findings suggest that the Gema Hajj program contributes to character development based on the Graduate Profile Dimensions. However, further strengthening of several dimensions is still required to achieve more balanced and comprehensive character development.